The Use of Drilling Techniques Integrated with Technology to Improve Students’ Vocabulary Mastery - Merdani, Ni Luh; Dewi, Kadek Sintya; Mahendrayana, Gede (English Education Department STKIP Agama Hindu Singaraja, 2024)
The purpose of this study is to improve students' vocabulary mastery with the use of drilling techniques integrated with technology through English vocabulary videos and to find out students' opinions regarding the implementation of drilling techniques through vocabulary videos. This research is a Classroom Action Research (PTK). The subjects in this study were fourth-grade students of An Elementary School in Bangli Regency, Bali, totaling 25 students. There were two data collection techniques: vocabulary tests and student interviews. The research procedure includes stages: planning, action, observation, and reflection. Based on the study's results, it can be concluded that using drilling techniques integrated with technology through vocabulary videos can improve vocabulary mastery in students. This is evidenced by the results of student scores from the pre-test with a mean score of 57, which increased in cycle I to 74, and in cycle II increased to 86. In addition, students' opinions related to the implementation in class or online said that the use of drilling techniques integrated with technology through vocabulary videos was exciting and fun; besides that, students also felt motivated and more enthusiastic in learning, and of course, it could improve students' vocabulary mastery. Therefore, it can be concluded that using drilling techniques integrated with technology through vocabulary videos can improve vocabulary mastery in students at An Elementary School in Bangli Regency, Bali.